Pemanfaatan Google Clasroom untuk Mengatasi Masalah Pembelajaran di Masa Pandemi - Supriadi, Irwin; Gumilar, Agung Cahya; Sukmana, Nano (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2023)
The Covid-19 pandemic that has occurred since 2019 has hit various sectors of life, including the economy, society, culture, health, and also education. In the world of education, all schools began to close, and after that, there was a massive change in educational methods. One of these changes is the method of online learning education. One of the schools that have experienced the impact of the Covid-19 pandemic is the Rancakasumba 06 State Elementary School (SDN Rancakasumba 06) which is in Rancakasumba Village, Solokanjeruk District, Bandung Regency. The problem at SDN Rancakasumba 06 is that the teachers at SDN Rancakasumba 06 know about the Google Classroom application but do not know more about the existing features of the Google Classroom application and do not know how to use comprehensively. The program in this PKM adapts the in-service training program which is a training or coaching that provides an opportunity for a teacher to get performance development through training and mentoring. Face-to-face meetings are carried out using the lecture (presentation) method, demonstrations, and discussions followed by exercises/practices for creating a Google account, using Google Classroom as a learning medium, and exploring its features in it. With community service activities, the technology adaptation ability of SDN Rancakasumba 06 teachers in utilizing the Google Class Room as a learning medium can be improved.